Pharmacogenetic Predictors of Methylphenidate Dose-Response in Attention-Deficit/Hyperactivity Disorder - Froehlich, Tanya E. (2011)
OBJECTIVE: Due to significant individual variability in Attention Deficit/Hyperactivity Disorder (ADHD) medication response, there is increasing interest in identifying genetic predictors of treatment effects. This study examines the role of 4 catecholamine-related candidate genes in moderating methylphenidate (MPH) dose-response. METHOD: 89 stimulant-naïve children with ADHD aged 7–11 participated in a randomized, double-blind, crossover trial of long-acting MPH. Parents and teachers assessed each child’s response on placebo and three MPH dosage levels using the Vanderbilt ADHD rating scales. Children were genotyped for polymorphisms in the dopamine transporter’s (DAT) 3’ untranslated region, dopamine receptor D(4)‘s (DRD4) exon 3, catechol-O-methyltransferase’s (COMT) codon 158, and adrenergic α(2A)-receptor’s (ADRA2A) promoter. Linear mixed models evaluated gene, dose (mg/kg/day), and gene*dose effects on inattentive and hyperactive-impulsive domain outcomes. RESULTS: The most statistically significant gene*dose interactions were observed on hyperactive-impulsive symptoms for DRD4 and DAT polymorphisms, with participants lacking the DAT 10-repeat allele experiencing greater improvements in symptoms with increasing dose compared to 10-repeat carriers (p=0.008), and those lacking the DRD4 4-repeat allele showing less improvement across MPH doses compared to 4-repeat carriers (p=0.02). CONCLUSIONS: This study suggests that DAT and DRD4 polymorphisms may be associated with individual variability in methylphenidate dose-response, although further research in larger samples is required to confirm these findings and their clinical utility.